2018
DOI: 10.1002/jemt.23073
|View full text |Cite
|
Sign up to set email alerts
|

Enamel sample preparation for AFM: Influence on roughness and morphology

Abstract: Human dental enamel is organized by prisms that are structured between 3 and 6 µm in diameter. Determining the relationships between different treatments on the surface of enamel using ultrastructural analysis is the purpose of many in vitro experiments. Different sample pretreatments have been reported in the literature. Grinding and polishing are common procedures for enamel preparation. They provide a flat and standardized surface, which is imperative for the use of some techniques such as ATR‐FTIR. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In order to create an artificial demineralized lesion, 37% phosphoric acid was used, as suggested by Sorozini [29]. Within the limitations of this study, this was considered sufficient, as it has been shown that absolute simulation of oral conditions is almost impossible due to other variables, including the speed of saliva flow and its buffering ability, dynamic pH cycles in the mouth, and behavioral changes [28,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In order to create an artificial demineralized lesion, 37% phosphoric acid was used, as suggested by Sorozini [29]. Within the limitations of this study, this was considered sufficient, as it has been shown that absolute simulation of oral conditions is almost impossible due to other variables, including the speed of saliva flow and its buffering ability, dynamic pH cycles in the mouth, and behavioral changes [28,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…This study was first designed with the purpose of evaluating dental enamel specimens' roughness submitted to surface treatments without flattening (Sorozini et al, ), in different moments (repeated measures), without the necessity of metallization. Although the most appropriate methods have been discussed (Fischer et al, ; Talu et al, ), there was still a gap in this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Dental enamel roughness analysis by AFM and contact profilometry are quantitative methods that demand flat specimen surfaces to avoid reading errors on the peaks and valleys (axis Z) or noises, depending on the topographic characteristics. However, a flattened specimen may lead to biased results as the subsurface enamel layer is less mineralized and more susceptible to the effects of treatments (Sorozini, Perez, & Rocha, ) while the whole dental surface properly simulates the clinical reality, increasing the validity and scientific value (Mullan, Mylonas, Parkinson, Bartlett, & Austin, ). Furthermore, the location of the area of interest for the repeated measures depends on the operator care due to the lack of precise tools for delimitation.…”
Section: Introductionmentioning
confidence: 99%
“…A frequently overlooked factor in the interpretation of enamel morphology and bond strength is the enamel surface preparation method. Surfaces are normally standardized through silicon carbide grinding and polishing to minimize differences in collected enamel specimens, standardize smear layers, and accommodate the reality that many bond fatigue testing experimental setups require flat surfaces (Sorozini, dos Reis Perez, & Rocha, ; Tsujimoto, Barkmeier, et al, ). However, this process can fragment and then compact hydroxyapatite crystals on the surface of enamel and affect surface topography and its associated measures (Sai et al, ).…”
Section: Discussionmentioning
confidence: 99%